Pipeline condition assessment and finite element modeling of mechano-electrochemical interaction between corrosion defects with varied orientations on pipelines. (June 2023) - Qin, Guojin; Huang, Yunfei; Wang, Yihuan; Frank Cheng, Y.
Highlights: Developed new multiphysics coupled models for pipeline condition assessment. Modeled multiphysics coupled effect between multiple defects with varied orientations. Quantified varied magnitude of multiphysics coupled effect on pipeline conditions. Discussed new recommended practice for pipeline asset management. Abstract: Multiple corrosion defects located in varied orientations are common on pipelines, significantly impacting pipeline conditions. In this work, 3D finite element (FE) based multi-physics field coupling models were developed to model mechano-electrochemical (M−E) interaction between corrosion defects with varied orientations and its effect on pipeline conditions. The effects of the parameters, including defect geometries, operating conditions, and the relative positions and spacings between the defects, were determined. The results demonstrated that, the strongest M−E interaction occurred between defects when the longitudinal or circumferential spacing is 0, causing high-level local stress concentration and the anodic current density (i.e., corrosion rate) at the corrosion defects. As the defects gradually overlapped or separated from each other on the pipe surface, the magnitude of the M−E interaction decreased. The interaction between defects even disappeared when the longitudinal or circumferential spacing between defects reached 96 mm or 72 mm, respectively, and the defects can be assessed separately. An increased internal pressure led to local plasticity deformation and anodic current density concentration occurring at the inner edge of the defects and defect adjacent area. For example, the maximum anodic current density increased by 56.4% when the internal pressure increased from 12 MPa to 17 MPa. It was also observed that M−E interaction between defects disappeared if the defects were shorter than 48 mm or shallower than 8 mm. Sensitivity analysis demonstrated that the degree of M−E interaction was most sensitive to circumferential spacing, followed by defect depth, defect length, longitudinal spacing, and internal pressure.